2009
DOI: 10.1111/j.1532-5415.2009.02402.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Influenza Vaccination of Nursing Home Staff on Mortality of Residents: A Cluster‐Randomized Trial

Abstract: These results support influenza vaccination of staff caring for institutionalized elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
187
0
12

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(201 citation statements)
references
References 29 publications
2
187
0
12
Order By: Relevance
“…Several observational studies and randomized clinical trials have shown that seasonal influenza vaccination of healthcare professionals in nursing homes and hospitals can reduce influenza-like-illness, and influenza in their patients [44][45][46][47][48][49].…”
Section: Strategies For Improving Vaccination Effectiveness In the Elmentioning
confidence: 99%
“…Several observational studies and randomized clinical trials have shown that seasonal influenza vaccination of healthcare professionals in nursing homes and hospitals can reduce influenza-like-illness, and influenza in their patients [44][45][46][47][48][49].…”
Section: Strategies For Improving Vaccination Effectiveness In the Elmentioning
confidence: 99%
“…22 For instance, while all-cause mortality was used as the primary outcome in all four trials, it was argued that influenza incidence (laboratory-confirmed) and influenza-specific mortality are more appropriate. [8][9][10][11] In fact, a Cochrane Database Systematic Review did not identify an effect of HCW vaccination on laboratory-confirmed influenza or related complications (lower respiratory tract infections and hospitalization) in elderly patients. 24 Second, the trials did not explicitly describe important cointerventions (i.e., handwashing, early detection of influenza among patients presenting with an influenza-like illness, and prompt use of antivirals.)…”
Section: Outcomementioning
confidence: 99%
“…7 Four randomized controlled studies in chronic care settings have demonstrated a 20%-40% reduction in patient mortality rates by improving HCW vaccination rates. [8][9][10][11] According to the British Columbia Centre for Disease Control, increasing the proportion of HCWs who receive influenza vaccination by 40% would lower the annual mortality (attributed to influenza) of nursing home residents from 1.3% to 0.5%. 12 There is conflicting evidence specifically demonstrating a reduction in influenza transmission due to HCW vaccination.…”
mentioning
confidence: 99%
“…When only taking into consideration studies that scored 3 or higher on the JADAD scale 5,14,15,16,17,18 5). …”
Section: Identification Of Relevant Researchmentioning
confidence: 99%
“…In addition, considering only high quality studies published after 2007 2009, 18 Abramson 2010 (Fig. 9).…”
Section: Identification Of Relevant Researchmentioning
confidence: 99%